In situ incorporation of magnetic nanoparticles within the carboxymethyl cellulose hydrogels enables dye removal. Issue 4 (16th May 2022) - Singh, Nirbhai; Yadav, Saurabh; Mehta, Surinder K.; Dan, Abhijit
Abstract: Herein, we report a novel approach for the synthesis of magnetic nanoparticle (Fe3 O4 ) incorporated carboxymethyl cellulose (CMC) hydrogel nanocomposites (CMC-Fe3 O4 ) that involves in-situ mineralization of Fe 2+ /Fe 3+ ions in a hydrogel network. In this protocol, first, pure CMC hydrogel was prepared using citric acid as a cross-linker. Subsequently, the Fe3 O4 nanoparticles were allowed to form inside the hydrogel matrix by a co-precipitation method. The resulting materials were characterized by various physical techniques, viz., Fourier transform infrared (FTIR) spectra, X-ray diffraction (XRD), thermal gravimetric analysis (TGA), vibrating sample magnetometry (VSM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer–Emmett–Teller (BET) analysis. We find that this strategy offered unique characteristic features, including morphology and structural order of the nanocomposites. We further explored the feasibility of using the prepared materials in the clearance of methylene blue (MB) from aqueous solution making the use of magnetic property of the nanocomposites. The adsorption kinetics followed the pseudo-second-order and the intraparticle diffusion models. The equilibrium adsorption capacity could be explained by the Freundlich and Halsey models, indicating heterogeneous adsorption with a multilayer coverage of the dyes. The nanocomposites maintained their high adsorption capacity after five successive cycles, thus providing an excellent cost-effective material for dye removal. Graphical Abstract: UF0001